Efficacy of switching to aripiprazole and ziprasidone on clinical and metabolic profile among schizophrenic patients with metabolic syndrome / Mas Ayu Binti Said - Mas Ayu, Said (2013)
Introduction: Schizophrenia is a devastating mental illness that impairs mental and social functioning and often leads to the development of co-morbid diseases. They are at greater risk for metabolic dysfunctions than other individuals due to a number of reasons, including inactive lifestyle, poor dietary choices, and side effects of antipsychotic medications. Atypical antipsychotics were reported to be associated with increased risk of hyperglycaemia and hyperlipidemia, and subsequently increase the risk of metabolic syndrome. However, ziprasidone and aripiprazole have a favourable metabolic profile. Objectives: i) To determine the prevalence of metabolic syndrome and its components among schizophrenia patients. ii) To determine the improvement and reversibility of metabolic syndrome, its components and lipid profiles after switching to aripiprazole or ziprasidone. iii) To determine the safety and efficacy of aripiprazole and ziprasidone in the treatment of schizophrenia patients with metabolic syndrome. Methodology:Screening -The study was conducted at four mental institutions and four general hospitals. Study population were schizophrenia patients aged between 18 and 65 years old, who met the DSM-IV TR criteria for schizophrenia. Patients should receive antipsychotic treatment for at least 1 year and were not on mood stabilizer. Metabolic syndrome was defined by using the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) criteria-modified for Asian waist circumference. Randomized double-blind controlled trial was conducted for 6-month after screening.The dose of aripiprazole and ziprasidone, can be either increased or reduced based on clinical assessment. The total daily dosage of ziprasidone ranges from 80mg - 160mg.The total daily dosage of aripiprazole ranges from 10mg - 30 mg. The outcome measures included body mass index (BMI), waist circumference, blood v pressure(BP), fasting blood sugar (FBS) and lipid profile, adverse effects monitoring and clinical rating scale such as Positive and Negative Symptoms Scale (PANSS), Clinical Global Impression Scale (CGI), Abnormal Involuntary Movement Scale (AIMS), Barnes Akathasia Scale (BAS) and Simpson Angus Scale (SAS).Intention-to-treat analysis and mixed-effects model with repeated measures (MMRM) for statistical analysis were done. Results: A total of 527 patients were screened but only 270 schizophrenia patients fulfil all inclusion and did not have any exclusion criteria. The prevalence of metabolic syndrome was 46.7%. There was improvement in the prevalence of all metabolic syndrome component from baseline to 6-month after switching to aripiprazole or ziprasidone; waist circumference (aripiprazole 84.4% vs. 44.4%, ziprasizone 87.1% vs. 35.3%), HDL cholesterol (aripiprazole 54.4% vs. 33.3%, ziprasizone 52.9% vs. 23.5%), triglycerides (aripiprazole 50.0% vs. 21.1%, ziprasizone 37.6% vs. 12.9%), BP (aripiprazole 41.1% vs. 25.6%, ziprasizone 32.9% vs. 20.0%), FBS (aripiprazole 42.2% vs. 20.0%, ziprasizone 25.9% vs. 8.2%, p<0.05). Switching to either aripiprazole or ziprasidone cause statistically significant reduction in prevalence of metabolic syndrome after 6 month of treatment (aripiprazole 58.9% vs. 30.0%, ziprasizone 51.8% vs. 15.3%, p<0.05). There was statistically significant improvement in PANSS, CGI, BARS and SAS after switching to aripiprazole or ziprasidone. Conclusion: The prevalence of metabolic syndrome in schizophrenia patients receiving antipsychotic in Malaysia was very high. Switching to aripiprazole or ziprazidone was effective in reversing the metabolic syndrome and its components among schizophrenia patients who had metabolic syndrome.